The Association Between Physical Environmental Condition Of House With The Pneumonia On Children Under Five Years At Working Area Pati I Public Health Center Subdistrict Pati Regency - Eka Luvita Sari; - Suhartono; Tri Joko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
Background: Pneumonia is inflammation and swelling of lung tissue infection caused by inhalation of foreign particles or radiation. In 2012-2013, there were 1.096 pneumonia cases on children under five years at Pati regency. I Pati Public Health Center had the highest pneumonia cases on children under five years with total 524 cases. One of risk factor that influence pneumonia incidence on children under five years was physical environmental condition of house. This study aimed to determine the association between physical environmental condition of housing with pneumonia incidence on children under five years. Method: It was the explanatory research observational with case control approach. The sample in this research was children ages 12-59 months with pneumonia and take a medicine Pati I Public Health Center on September 2012-August 2013. Data collecting through survey used questioner, observation and direct measurement at field. Data analytical used Chi-Square statistic examination and the risk with Odds Ratio (OR). Result: The result showed significant association with room of density (p=0,000; OR=9,804), house of temperature (p= 0,010; OR= 12,571) natural lighting of house (p=0,000; OR=6,588), house of humidity (p=0,005; OR=8,734), room of humadity (p=0,001; OR=11,862) While house of density (pvalue= 0,609; OR=3,143), type of walls (p value = 0,053; OR=5,375), type of floors(p =0,064; OR=8,105), ventilation wide (p= 0,833; OR=0,836), room of temperature (p = 0,072; OR=4,000), dan natural lighting of room (p= 0,0091; OR=6,588) did not show significant association. Conclusion: This study concludes that the need to improve the physical condition of the home environment, especially the habit of opening the window and healthy home ventilation standards